The Contribution Of United Nations Industrial Development Organization (UNIDO) In Sustainable Fisheries Development In Indonesia 2019-2023 - Hidatyat, Regga Fajar; Rahayu, Dini Septyana; Susilowati, Ida (Mediasi Journal of International Relations, 2024)
This type of research is qualitative research, using Liberal Institutional theory and the concept of SDGs. Data collection was conducted through desk research and secondary data techniques to obtain the necessary data. The Miles and Huberman model identifies three main processes in data analysis: data reduction, data presentation, and conclusion drawing. This research was conducted as an effort to find out the extent of UNIDO's contribution and implications in the development of the sustainable fisheries sector and towards sustainable development (SDGs) No. 14 in Indonesia in 2019-2023. This research provides academic benefits by enriching the literature on the role of international institutions in the development of sustainable fisheries sector. Practically, the results of this study serve as a guide for policy makers and fisheries industry players in improving quality and sustainability standards. The implementation of Indonesia's GQSP has been going well in all sectors, as a whole. Based on the targeted Key Performance Indicators (KPIs), GQSP has achieved 100% of 52 Output KPIs, 80% of 33 Outcome KPIs and 67.3% of 7 Impact KPIs. In its contribution to improving quality infrastructure and services, strengthening producers and value chains, and building a culture of quality, these aspects have a major contribution. This can be seen from the growth of Indonesian fishery product exports over the past five years (2017-2022). In 2017 Indonesia reached an export figure of 1.08 million tons worth USD 4.52 billion and to 1.22 million tons worth USD 6.24 billion in 2022. UNIDO through GQSP Indonesia has successfully improved the overall quality of Indonesia's fisheries industry. NQIS has brought significant positive impacts in various aspects of fisheries industry development.